2011
DOI: 10.1177/1947601911431081
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Neoplasia Differentially Expressed (CRNDE), a Novel Gene with Elevated Expression in Colorectal Adenomas and Adenocarcinomas

Abstract: An uncharacterized gene locus (Chr16:hCG_1815491), now named colorectal neoplasia differentially expressed (gene symbol CRNDE), is activated early in colorectal neoplasia. The locus is unrelated to any known protein-coding gene. Microarray analysis of 454 tissue specimens (discovery) and 68 previously untested specimens (validation) showed elevated expression of CRNDE in >90% of colorectal adenomas and adenocarcinomas. These findings were confirmed and extended by exon microarray studies and RT-PCR assays. CRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
228
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(232 citation statements)
references
References 39 publications
4
228
0
Order By: Relevance
“…As the CRNDE promoter resides in the same CpG island as that of the adjacent IRX5 gene, methylation of the promoter region results in coordinated expression. 32 Similarly, we found that the highest positive correlation (0.77) for the lncRNA FENDRR was with a protein coding gene, FOXF1, transcribed bidirectionally on the opposite strand. 35 Additionally, the lncRNA HOTAIR, which resides in a HOXC gene cluster, is known to be co-expressed with HOXC genes, and overlaps HOXC11, displayed its highest positive correlation with multiple HOXC genes including HOXC11 (0.86), HOXC10 (0.72), HOXC13 (0.66), HOXC8 (0.44), and HOXC9 (0.38).…”
Section: Prediction Of Onco-lncrna Functionmentioning
confidence: 74%
“…As the CRNDE promoter resides in the same CpG island as that of the adjacent IRX5 gene, methylation of the promoter region results in coordinated expression. 32 Similarly, we found that the highest positive correlation (0.77) for the lncRNA FENDRR was with a protein coding gene, FOXF1, transcribed bidirectionally on the opposite strand. 35 Additionally, the lncRNA HOTAIR, which resides in a HOXC gene cluster, is known to be co-expressed with HOXC genes, and overlaps HOXC11, displayed its highest positive correlation with multiple HOXC genes including HOXC11 (0.86), HOXC10 (0.72), HOXC13 (0.66), HOXC8 (0.44), and HOXC9 (0.38).…”
Section: Prediction Of Onco-lncrna Functionmentioning
confidence: 74%
“…6,7,[79][80][81] Notably, similar to other nucleic acids, lncRNAs can also be present in peripheral blood components, such as serum, plasma, and peripheral blood mononuclear cells. [82][83][84] The peripheral lncRNA profiles may potentially contribute to the characterization of novel biomarkers for CRC patients. Indeed, some lncRNAs appear to have strong diagnostic potential as blood biomarkers for colorectal neoplasia.…”
Section: Tumor Diagnosismentioning
confidence: 99%
“…For example, the expression of colorectal neoplasia differentially expressed-h in the plasma had a sensitivity of 87% and a specificity of 93% for detecting CRC. 82 It is likely that circulating lncRNAs may represent new, relatively non-invasive molecular markers of tumor activity. However, no lncRNA-based diagnostics have been developed for use in CRC as of yet.…”
Section: Tumor Diagnosismentioning
confidence: 99%
“…LncRNAs are involved in various physiological and cellular processes such as development, growth, cell cycle progression, differentiation, inflammation, tumorigenesis, migration and invasion [9-12, 21-23]. Colorectal neoplasia differentially expressed (CRNDE) was initially identified as an lncRNA in colorectal cancer and was found to be located on chromosome 16, which is important in the proliferation, migration, and invasion of colorectal tumor cells [24-28]. Nonetheless, little is known regarding the biological role of CNRDE in the process of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%